2020
DOI: 10.3389/fnagi.2020.580199
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosome microRNAs as Diagnostic Biomarkers of Dementia

Abstract: Dementia is a syndrome of acquired cognitive impairment that leads to a significant decline in a patient's daily life, ability to learn, and the ability to communicate with others. Dementia occurs in many diseases, including Alzheimer's disease (AD), dementia with Lewy bodies, frontotemporal dementia, and Parkinson's disease dementia (PDD). Although the analysis of biomarkers in the cerebrospinal fluid (CSF) and peripheral blood physicochemical analysis can indicate neurological impairment, there are currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…Numerous studies have confirmed that exosome-derived proteins, lncRNAs or miRNAs can be stably detected in body fluids (He et al, 2018 ). These molecules have been considered as novel biomarkers for the diagnosis of neurodegenerative diseases, including AD (Dong et al, 2020 ); however, the potential diagnostic value of quantifying exosome-derived biomarkers for AD or MCI has not previously been confirmed through a systematic analysis. Thus, this meta-analysis was performed to elucidate the diagnostic value of exosome-derived biomarkers in AD or MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that exosome-derived proteins, lncRNAs or miRNAs can be stably detected in body fluids (He et al, 2018 ). These molecules have been considered as novel biomarkers for the diagnosis of neurodegenerative diseases, including AD (Dong et al, 2020 ); however, the potential diagnostic value of quantifying exosome-derived biomarkers for AD or MCI has not previously been confirmed through a systematic analysis. Thus, this meta-analysis was performed to elucidate the diagnostic value of exosome-derived biomarkers in AD or MCI.…”
Section: Discussionmentioning
confidence: 99%
“…However, some inconsistent results have been reported; for instance, results suggest CSF exosomes from AD patients exhibit increased levels of miR-125b-5p, yet data from another study indicate its levels in plasma exosomes are associated with poor cognitive performance ( Rani et al, 2017 ; McKeever et al, 2018 ). As there appears to be minimal concordance across studies, the application of exosomal miRNAs as reliable diagnostic indicators may currently be limited to within particular individuals ( Dong et al, 2020 ).…”
Section: Using Exosomes To Improve Outcomes In Cognitve Declinementioning
confidence: 99%
“…AD differential diagnosis. For a comprehensive review of circulating exosomes’ miRNAs differently expressed in dementias and useful in differential diagnosis see [ 143 ].…”
Section: Mirna Expression Profilingmentioning
confidence: 99%